Games and arts as strategies for environmental education in school context - Ruiz, Juliana; Schwartz, Gisele Maria (Journal of Physical Education (Maringá), 2008)
The present qualitative study aimed at contributing for the reflection on the Environmental Education process in school context, focusing the importance of aesthetic and playfull elements as sensitizing and awareness factors, considering their positive influence on favoring a possible change in values and attitudes, and stimulating the diffusion of conservationists and more human postures.